Zona pellucida-binding protein 2 (ZPBP2) and several proteins containing BX7B motifs in human sperm may have hyaluronic acid binding or recognition properties. (8th November 2017) - Torabi, F; Bogle, O A; Estanyol, J M; Oliva, R; Miller, D
Abstract: STUDY QUESTION: Are there novel hyaladherins in human sperm? SUMMARY ANSWER: Zona pellucida-binding protein 2 (ZPBP2), containing a Link-like hyaluronic acid (HA)-binding domain, and several other proteins containing BX7B motifs, such as ADAM32 and Midkine, may be novel hyaladherins with HA-binding properties. WHAT IS KNOWN ALREADY: HA-binding proteins (hyaladherins), which can bind HA surrounding the cumulus-oophorus complex, are distinct from hyases such as PH 20 (SPAM1) and are expressed by mature spermatozoa. Although HABP1 and CD44 are reasonably well characterized hyaladherins and the former has been implicated in sperm-oocyte interactions, the overall significance of sperm hyaladherins for male fertility is still poorly understood. STUDY DESIGN, SIZE, DURATION: This was a laboratory-based investigation into human sperm hyaladherins undertaken as part of a three year PhD programme sponsored by the EU Marie Curie Training network, Reprotrain. PARTICIPANTS/MATERIALS, SETTING, METHODS: Protein homogenates of sperm obtained from young men of unknown fertility ( N = 4) were partitioned into HA-binding and non-binding fractions by a protein affinity 'panning' method; their subsequent characterization was by liquid chromatography-tandem mass spectrometry (LC-MS-MS) and partitioning behaviour was confirmed by western blotting. Sequences of proteins from both fractions were submitted to PDBsum to look for orthologous entries (PDB codes) and all returned codes were queried against the matching protein using SAS (Sequences Annotated by Structure) looking for structural similarities between them. A systematic search for other common features of hyaladherins was also undertaken. MAIN RESULTS AND THE ROLE OF CHANCE: The presence of BX7B sequence motifs found in several well-described hyaladherins including RHAMM was used to assess efficacy of potential hyaladherin partitioning by the HA substrate. The data showed that 50% (14/28) and 34.5% (28/81) of proteins in the bound and unbound fractions, respectively, contained these motifs (one-tailed Z -score = 1.45; P = 0.074), indicating weak discrimination by the substrate. Querying PDBsum with sequences for all bound proteins returned several PDB codes matching ZPBP2 with the HA-binding Link domain of the hyaladherin, CD44. Western blot analysis confirmed the affinity partitioning of proteins indicated by the LC-MS/MS results, with ADAM32 (containing two BX7B motifs) and ZPBP2 (containing a Link-like HA-binding domain) present only in the binding fraction. There remains the possibility that the putative hyaladherins uncovered by this study were coincidentally enriched by HA-binding. LARGE SCALE DATA: The full proteomics data set is available on request. LIMITATIONS REASONS FOR CAUTION: The protein extraction methods or the HA substrate used to pan them in this study were probably not ideal, as hyaladherins expected to be present in sperm homogenates (such as CD44 and RHAMM) were not detected. WIDER IMPLICATIONS OF THE FINDINGS: The results provide evidence that ZPBP2, found only in the bound fraction, may have hyaladherin-like properties, which could reflect the evolutionary background context of contemporary sperm-oocyte interaction mechanisms. STUDY FUNDING AND COMPETING INTEREST(S): An EU Marie Curie Sklodowska Initial Training Network Scholarship, supporting Ms Torabi, is gratefully acknowledged. This project was also supported and funded by the Efficacy and Mechanism Evaluation Programme, a UK MRC and NIHR partnership (Grant No 11/14/ 34). There is no conflict of interest in relation to this work.